(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Philosophy is a product of human thought, and each civilization has contributed to it. Eastern philosophy is considered one of the oldest and most profound systems of thought. It illuminates such complex concepts as man and nature, spirit and matter, good and evil, freedom and destiny. India, China, Iran, and Central Asia are historical centers of Eastern philosophy. The philosophical views formed in these regions determined not only religious and moral values, but also political, social, and scientific ideas.